Evaluating the utility of plasma Atherogenic Index among several atherogenic parameters in patients with chronic renal Failure on maintenance hemodialysis - Al-Tai, Wafa F.; Jaffer, Elham M. H.; Ali, Zean A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Patients with chronic renal failure undergoing longterm hemodialysis (HD) are prone to atherosclerosis and at increased risk of developing cardiovascular diseases. Objective: The objective of this study is to compare atherogenic index of plasma (AIP) in predicting the risk of cardiovascular disease (CVD) in patients with chronic renal failure (CRF) on regular hemodialysis, when associated with other chronic diseases. Patients and methods: A total of forty male patients with CRF on hemodialysis, matched in, age, body mass index BMI, and duration of hemodialysis were enrolled. They were grouped as group 1 (G1) includes eleven subjects with CRF without (hypertension and / or diabetes) groups 2 (G2) fourteen CRF subjects with hypertension and group 3 (G3) fifteen CRF subjects with diabetes. As a control group, eighteen healthy male subjects were included with special exclusion criteria. The plasma total cholesterol TC, triglyceride TG, and high density lipoprotein-cholesterol HDL-C were estimated using spectrophotometry methods. While low density lipoprotein-cholesterol LDL-c, and AIP were calculated using special formulas. Statistical analysis was performed by the student t-test. Results: The results of the study revealed significant increase in TC and TG, with significant decrease in HDL-c for all patient groups compared to control. No significant difference in LDL-c of G1 compared to control was found, while significant increase in LDL-c of G2 and G3 was found when compared to G1 or control. The AIP values were (0.42 ± 0.19 vs 0.43 ± 0.17; P>0.05) for G1 and G2 respectively, that showed no significant difference of atherogenic risk between these groups. Conclusions: These results concluded that AIP seems to be superior to LDL-c in predicting the risk for CVD in CRF groups on hemodialysis and those at the highest risk when CRF coupled with diabetes.